2018
DOI: 10.3390/s18051650
|View full text |Cite
|
Sign up to set email alerts
|

Random Weighting, Strong Tracking, and Unscented Kalman Filter for Soft Tissue Characterization

Abstract: This paper presents a new nonlinear filtering method based on the Hunt-Crossley model for online nonlinear soft tissue characterization. This method overcomes the problem of performance degradation in the unscented Kalman filter due to contact model error. It adopts the concept of Mahalanobis distance to identify contact model error, and further incorporates a scaling factor in predicted state covariance to compensate identified model error. This scaling factor is determined according to the principle of innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The Kalman Filter is a Linear Quadratic Estimation (LQE) method that is widely used in various fields, including navigation [ 10 ], signal processing [ 11 ], control systems [ 12 ], biological tissue identification [ 13 ], etc. The Kalman Filter is based on the state–space model, and for linear systems and Gaussian noise, this model is usually represented by the following two equations [ 8 ]:…”
Section: Methodsmentioning
confidence: 99%
“…The Kalman Filter is a Linear Quadratic Estimation (LQE) method that is widely used in various fields, including navigation [ 10 ], signal processing [ 11 ], control systems [ 12 ], biological tissue identification [ 13 ], etc. The Kalman Filter is based on the state–space model, and for linear systems and Gaussian noise, this model is usually represented by the following two equations [ 8 ]:…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above, the adaptive scaling factor Φ can be attained by matching the predicted state covariance given by (17) with its theoretical value given by (22):…”
Section: Recursive Adaptive Unscented Kalman Filtermentioning
confidence: 99%
“…The authors also studied a UKF based on the H-C model for soft tissue characterization [16], but without considering the UKF requirement of accurate system models. Just recently, the authors reported an improved UKF to handle the error of the H-C contact model using the scaling factor [17]. However, this method is based on the assumption that the measurement model is accurate, which does not correspond to the realworld situation with errors involved in both contact and measurement models.…”
Section: Introductionmentioning
confidence: 99%